How Can Surgeonfish Help Pediatric Surgeons? A Pilot Study Investigating the Antinociceptive Effect of Fish Aquariums in Adult Volunteers - Matthieu Sanchez; Marion Delpont; Manon Bachy; Reda Kabbaj; Daniel Annequin; Raphaël Vialle (Pain Research and Management)
BACKGROUND: Multiple distraction strategies have been proposed to reduce the incidence of anxiety and pain in children. Animal-assisted therapy is acknowledged and used in children as an adjunctive treatment with cognitive, physical, psychosocial and spiritual benefits.